The internationalization of firms. Case studies from the Nürnberg Metropolitan Region. 2nd ed. - (:unkn) unknown (Hampp, 2018)
Der Band enthält 17 Fallstudien von Unternehmen mit Sitz in der Metropolregion Nürnberg und ihren internationalen Aktivitäten. Die Bandbreite reicht von frühen Internationalisierungsstrategien im Mittelalter bis zu den Folgen des Brexit auf laufende Geschäftsaktivitäten. Die Fallstudien decken ein breites Spektrum von Branchen ab, von High-Tech- und Industriesektoren über Dienstleister, Non-Profit-Organisationen bis hin zu Hochschulen.

The Nürnberg Metropolitan Region is one of the most powerful economic regions in Europe. Several large and renowned multinational corporations, as well as many impressive family-owned firms and hidden champions, have their headquarters here. This volume contains 17 case studies of companies based in this region and their international operations. The scope reaches from the early internationalization strategies of the Tucher in the Middle Ages to the consequences of the Brexit on current business activities. The case studies cover an extensive range of industries, from high-tech and industrial sectors to service providers, non-profit organizations and university spin-offs.
Keywords: Metropolregion; Wirtschaftsregion; Regionalwirtschaft; Unternehmen; Außenhandel; Internationalisierung; Globalisierung; Wirtschaftsgeschichte; Firmengeschichte; Fallstudie